The Cell Cycle-Associated Protein CDKN2A May Promotes Colorectal Cancer Cell Metastasis by Inducing Epithelial-Mesenchymal Transition - Shi, Wei-Kun; Li, Yun-Hao; Bai, Xue-Shan; Lin, Guo-Le (Frontiers in Oncology, 2022)
Colorectal cancer (CRC) is a common gastrointestinal malignancy, and recurrence and metastasis contribute considerably to its high mortality. It is well known that the epithelial-mesenchymal transition (EMT) accelerates the rate of cancer cell dissemination and migration, thus promoting cancer metastasis. Targeted therapy is a common modality for cancer treatment, and it can play a role in inhibiting cancer progression. In this study, bioinformatics was used to search for genes associated with the prognosis of CRC. First, differential analysis was performed on colon and rectal cancer samples to obtain 2,840 and 3,177 differentially expressed genes (DEGs), respectively. A Venn diagram was then used to identify 262 overlapping genes from the two groups of DEGs and EMT-related genes. The overlapping genes were subjected to batch survival analysis and batch expression analysis successively, and nine genes were obtained whose high expression in CRC led to a poor prognosis. The least absolute shrinkage and selection operator (LASSO) prognostic model was then constructed to obtain the risk score formula. A nomogram was constructed to seek prognostic independent factors to obtain CDKN2A. Finally, CCK-8 assay, flow cytometry and western blotting assays were performed to analyze the cellular biological function of CDKN2A. The results showed that knockdown of CDKN2A expression inhibited HT-29 cell proliferation, promoted apoptosis and cell cycle progression, and affected the EMT process in CRC.